Determining soil water characteristic curve of lime treated loess using multiscale structure fractal characteristic - Xiaojun Li (Nature Portfolio, 2020)
Abstract Soil–Water characteristic Curve (SWCC) is meant to describe the mechanical behavior of unsaturated soil. The present paper focuses on the internal multi-scale microstructure of Xining untreated loess and lime-treated loess with the use of scanning electron microscopy (SEM) and image processing technique. A new SWCC model was presented based on the fractal dimension of pore size distribution. The SWCC of untreated loess was calculated from fractal dimension and fitted well with curve tested from Fredlund SWCC device. The SWCC of lime-treated loess was then calculated. Two curves of Xining untreated loess and lime-treated loess have been compared and reasons for the difference have also been discussed. The results indicate that the content of large pores in lime-treated loess decreased and the content of micro-pore increased. The bracket pores were changed into cement pores. The pore fractal dimension D of Xining untreated loess is 1.39 and the pore fractal dimension D of Xining lime-treated loess is 1.53. Air-entry value of untreated loess is 12.16 kPa, while lime-treated Loess—35.15 kPa. In transition region, matric suction of lime-treated loess was in the range of 35.15 kPa ~ 4000 kPa, while matric suction of untreated loess—12.16 kPa ~ 2600 kPa. The range of the transition region in lime-treated loess is larger than that in the loess, while in the range of saturation region, the reverse applies. Under the condition of the same matrix suction, the saturation of lime-treated loess is greater than that of untreated loess. In the residual region, the difference of SWCC of soil samples is small.